(untitled) (Journal for Studies in Humanities and Social Sciences, 2017)
This paper reports on a study carried out on organisational knowledge management (KM) practices in the Ministry of Gender Equality and Child Welfare (MGECW) in Namibia. The objectives of the study were: to explore knowledge sharing (KS), knowledge acquisition (KA), knowledge capture (KC), knowledge dissemination (KD), and knowledge transfer (KT) at MGECW; to determine barriers and enablers to organisational KM; to examine the work culture and attitudes of personnel which affect organisational KM and its practices; and to investigate how management supports organisational KM practices. The case study used a mixed methods approach. Two instruments were used to collect data, namely semi-structures interviews and questionnaires. The results reveal that organisational knowledge (OK) in the MGECW hinges on tacit and explicit OK and respondents had a comprehensive understanding of OK and KM, however, the management of OK was found to be informally practiced without KM structures in place and no structural procedures to encourage employees to share their OK. Organisational KD and KT practices showed a strong preference for the use of fax machines, telephones and face-to-face meetings as forms of dispensing and transferring OK. Same enablers of organisational KM in the MGECW included positive leadership (senior management), technology (im-proved ICT infrastructure), organisational culture, employee commitment and involvement, trust, social networking and teamwork. The study found lack of skills and technical support in ICT; poor ICT infrastructure; lack of motivation and reward systems; negative attitude of employees towards organisational KM practices; poor record management; lack of time and funds for training and equipment as barriers of organisational KM.